THE EFFECT OF MURATTAL AL QURAN ON STUDENT CONCENTRATION - Liza Oktaria; Rizky Novia Ramadhini; Devi Mellani; Zahra Amelya Putri; Afifah Khoirunnisa; Putri Sakinatul Kirom; Windi Arsela; Tyas Rahmawati; Gustia Nanda Elfitra Santi; Novanda rana Hanifa (Taqrib : Journal of Islamic Studies and Education, 2023)
This study aims to prove the effect of playing murattal Al-Quran on increasing concentration. The research subjects were female students of the Faculty of Psychology, Raden Fatah State Islamic University Palembang with the criteria of being 19-21 years old with 30 subjects. This study used a pretest-post-test control group design. The research instrument uses the Digit Span test. Data analysis was carried out quantitatively using the statistical test T test. In the experimental group, the results of the test data showed that the average concentration score before receiving treatment was 6.20, the average score after receiving treatment was 7.93. Whereas in the control group, the average score before treatment was 6.33, for the result after treatment was 7.27. From the data obtained, there is a difference in the average score of the experimental group and the control group. This proves that there is an influence on listening to murattal Al-Qur'an on increasing concentration.